Definitions of Scientific Terminology in Popular Science Books: An Examination of Definitional Chains. Issue 5 (October 2019) - Pilkington, Olga A.
This article explores scientific terminology in popular science books. It goes beyond existing approaches to definitions in popularizations to suggest a dual, macro and micro, structure for the majority of definitions. This dual structure manifests as chains of definitions that include prototypical, procedural, and figurative definitions. Analyzing the structure and functions of the chains (macro structure) and their individual components (micro structure), this article does not confirm the phenomenon of substitution observed by Myers yet suggests that even without the replacement of terminology popular science maintains the focus on the specific rather than the general.